Zika virus modulates arthropod histone methylation for its survival in mosquito cells. - Telvin Harrell; Swarnendu Basak; Hameeda Sultana; Girish Neelakanta (PLoS ONE)
Zika virus (ZIKV) is a mosquito-borne human pathogen that causes mild febrile illness in adults and severe neurological complications and microcephaly in newborns. Studies have reported that ZIKV modulates methylation of human and viral RNA critical for its replication in vertebrate cells. In this study, we show that ZIKV modulates mosquito S-adenosyl methionine (SAMe)-synthase, an enzyme involved in the production of SAMe (methyl donor), and histone methylation for its survival in mosquito cells. Reverse transcription quantitative PCR followed by immunoblotting analysis showed increased amounts of SAMe synthase at both RNA and protein levels, respectively, in C6/36 mosquito cells infected with ZIKV at day 1 post infection (p.i.). Increased levels of SAMe was noted upon ZIKV infection at day 1 p.i in mosquito cells. In addition, increased EZH2 histone methyl transferase-like gene transcripts and methylated histone (H3K27me3) levels were evident in mosquito cells upon ZIKV infection. Exogenous addition of SAMe to mosquito cells showed increased ZIKV loads and EZH2 histone methyl transferase-like gene transcript levels. Furthermore, treatment of mosquito cells with EZH2 inhibitor resulted in reduced histone methylation and ZIKV loads. Collectively, our study provides novel information in understanding the importance of SAMe and histone methylation in the survival of ZIKV in its arthropod vector.